BELAJAR AKUNTANSI DASAR DENGAN CARA MUDAH DAN MENYENANGKAN - Irianing Suparlinah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
Perumda Pasar Satria Purwokerto has the goal of playing an active role in assisting the availability of supply, stability and affordability of prices for staple goods in the Banyumas area. For this reason, efforts are being made to foster and empower Market Traders to increase Regional Original Income (PAD). Internally, Perumda's management also made self-improvement by empowering and increasing the competence of its employees. In the field of accounting, Perumda's management seeks to improve the accounting competence of its employees so that they are able to carry out their duties and responsibilities better. Accounting training is carried out to increase understanding and insight into accounting and transaction processing practices at Perumda Pasar Satria. This is deemed necessary by management to support the achievement of the goals of Perumda Pasar Satria. The first stage of accounting training has been carried out by providing insight and knowledge of accounting and manual transaction processing practices. Furthermore, training will be carried out to improve computer-based accounting competencies. Employees are expected to have accounting knowledge and skills, although not all of their work is directly related to the application of computer accounting.